Racemose Neurocysticercosis - Das, Rohit R.; Tekulve, Kristyn J.; Agarwal, Atul; Tormoehlen, Laura M. (Seminars in Neurology, 2012)
Neurocysticercosis is one of the most common infections of the central nervous system in the developing world. Most often, neurocysticerci are found in the brain parenchyma, at the gray–white matter junction. A rare form of neurocysticercosis is the development of cysts at the basal subarachnoid region, termed racemose neurocysticercosis.
Keywords: neurocysticercosis; Taenia solium; treatment; meningitis; basal